Use of health services by adult Latin American immigrants residing in Seville - González-López, José Rafael; Rodríguez-Gázquez, María de los Ángeles; Lomas-Campos, María de las Mercedes (Investigación y Educación en Enfermería, 2014)
Objective. This work sought to describe the use of health services by adult Latin American immigrants from Seville. Methodology. This was a descriptive cohort study with the participation of 190 adult Latin American immigrants from 25 to 44 years of age, residing in the city of Seville (Spain) in 2011. A self-report survey was applied. Results. Within the past year, 67% of the individuals have visited a physician and 23% have attended nursing consultation. A total of 14% of the immigrants who called on a healthcare center reported that their experience was worse than that of others. La annual prevalence by accidents was: 10% domestic, 4% traffic-related and 9% occupational; nearly half these accidents justified emergency care or hospitalization due to their severity. The logistic regression model revealed that health services were used mostly by: women, those in poor self-perceived health status, those with secondary level of education, the elderly, and those who were single. Conclusion. The population studied presents adequate use of health services, although it would be recommendable to implement prevention activities by nurses in the immigrant’s work and family environment to reduce the accident incidence described by this group.